ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI PERUBAHAN LABA PERUSAHAAN (Studi Empiris pada Perusahaan Jasa dan Perdagangan yang Terdaftar di Bursa Efek Indonesia) - Resa Setya Nugroho; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
Financial Ratio Analysis is analysis that is used to describe the relationship between two or more financial data with each other. Financial Ratio Analysis are often used to predict changes in earnings company.This research aims to examine the financial ratio analysis to predict changes incorporate profits and trade services listed on the Indonesia Stock Exchange(IDX) of 2009-2011. Rasio used in this study, were, Liquidity Ratios, Activity Ratios, Ratio Asset Utilization and Operating Performance Ratio.Methods of data collection in this study was conducted by the documentation. The type of data in this study is secondary data. Those data are financial statements published by the company on the Indonesian Stock Exchange (BEI). Financial statement data obtained from company financial statements published by the Indonesia Direct Exchange (IDX). The method of analysis used in this study is multiple regression. This study uses the data and trading services company listed on the Indonesia Stock Exchange (BEI) in the year 2009-2011. Sampling was done by purposive sampling technique. Number of samples taken in this study were 117.The results showed that the variables had a significant influence on the change in earnings is the ratio of asset utilization. Variable liquidity ratios, activity and operating performance changes donotaffectthecompany'searnings.